2010
DOI: 10.5391/ijfis.2010.10.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dynamic Load Model Parameters Using Particle Swarm Optimization

Abstract: This paper presents a method for estimating the parameters of dynamic models for induction motor dominating loads. Using particle swarm optimization, the method finds the adequate set of parameters that best fit the sampling data from the measurement for a period of time, minimizing the error of the outputs, active and reactive power demands and satisfying the steady-state error criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…7(d) shows the limited current value considering the rated current of the switching elements. According to the increase in the dclink current in the mode-2 section to increase the active power, it can be confirmed that the peak of the ac-side current reference is reduced by the current limit condition of (23). In the case of the mode-3 section to the grid-side undervoltage conditions, the active power is reduced by the current limitation condition considering the arm capacitor voltage ripple.…”
Section: Current Limit Methods Considering Sm Capacitor Voltage Ripplementioning
confidence: 62%
“…7(d) shows the limited current value considering the rated current of the switching elements. According to the increase in the dclink current in the mode-2 section to increase the active power, it can be confirmed that the peak of the ac-side current reference is reduced by the current limit condition of (23). In the case of the mode-3 section to the grid-side undervoltage conditions, the active power is reduced by the current limitation condition considering the arm capacitor voltage ripple.…”
Section: Current Limit Methods Considering Sm Capacitor Voltage Ripplementioning
confidence: 62%
“…The BP algorithm is suitable for solving the complicated nonlinear problem, but the algorithm usually falls into local minimum, resulting in training failure. In [26], the authors proposed a method for estimating the parameters of dynamic models for induction motor dominating loads. Based on PSO, the method finds the adequate set of parameters that best fit the sampling data from the measurement for a period of time, minimizing the error of the outputs and active and reactive power demands.…”
Section: Optimization Of Initial Value Of Adjustable Parametersmentioning
confidence: 99%